PENGARUH HARGA DAN FASILITAS PANTAI TERHADAP DAYA TARIK PENGUNJUNG WISATA PANTAI SEJARAH : (Studi Pada Pengunjung Pantai Sejarah Kecamatan Limapuluh Pesisir) - Marwah; Adlina, Hafiza; Siregar, Onan Marakali (Transpublika Publisher, 2022)
The development of tourism at this time is very fast, with the increase of transportation to visit an area is quite easy, the abundance of natural tourism potential and beauty in Indonesia encourages local and foreign tourists to travel in Indonesia. In addition to its natural potential, Indonesia also has tours that are made with quality that is very great, tourist destinations must have an attraction that can make visitors or tourists return to the tourist destination. The form of research used in this research is quantitative research with purposive sampling and use 100 respondents. The results of this research shows that the price variable (X1) has no significant effect on the attractiveness of Sejarah Beach visitors. Meanwhile, the beach facilities variable (X2) has a significant and simultaneous effect on the attractiveness of Sejarah Beach visitors. The coefficient of determination test shows that there is a fairly close relationship between price and facilities on the attraction of historical beach tourism visitors with an R-value of 0.853. Through the adjusted R square, it is also known that the price and facilities variables contribute 72.2% to the visitor attractiveness variable while the remaining 27.8% is influenced by other variables not mentioned in this study.